2021
DOI: 10.3389/fmed.2021.671658
|View full text |Cite
|
Sign up to set email alerts
|

Useful Ultrasonographic Parameters to Predict Difficult Laryngoscopy and Difficult Tracheal Intubation—A Systematic Review and Meta-Analysis

Abstract: Unexpected difficult airway management can cause significant morbidity and mortality in patients admitted for elective procedures. Ultrasonography is a promising tool for perioperative airway assessment, nevertheless it is still unclear which sonographic parameters are useful predictors of difficult laryngoscopy and tracheal intubation. To determine the ultrasonographic predictors of a difficult airway that could be applied for routine practice, a systematic review and meta-analysis was conducted. Literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 40 publications
3
39
0
1
Order By: Relevance
“…Second, some ultrasonographic parameters were not examined, such as skin to epiglottis and skin to hyoid distances. 33 Third, our results may not be applicable to non-Asian populations due to the ethnic differences in morphometric and airway characteristics. 34 Fourth, although the risk of difficult laryngoscopy, defined as a Cormack and Lehane’s grade III or IV, was as high as 21.3% in this study, all patients were intubated successfully by direct laryngoscopy.…”
Section: Discussionmentioning
confidence: 87%
“…Second, some ultrasonographic parameters were not examined, such as skin to epiglottis and skin to hyoid distances. 33 Third, our results may not be applicable to non-Asian populations due to the ethnic differences in morphometric and airway characteristics. 34 Fourth, although the risk of difficult laryngoscopy, defined as a Cormack and Lehane’s grade III or IV, was as high as 21.3% in this study, all patients were intubated successfully by direct laryngoscopy.…”
Section: Discussionmentioning
confidence: 87%
“…Airway ultrasound is promising in the prediction of a difficult laryngoscopy. A recent meta-analysis found robust test characteristics for prediction of a difficult laryngoscopy with significant sensitivity and specificity in adult patients using ultrasound ( 96 ). Ultrasound metrics evaluating anterior neck soft tissue thickness and mobility of the neck were found to be important predictors of a difficult laryngoscopy ( 96 ).…”
Section: Current State Of Critical Care Point-of-care Ultrasoundmentioning
confidence: 99%
“…A recent meta-analysis found robust test characteristics for prediction of a difficult laryngoscopy with significant sensitivity and specificity in adult patients using ultrasound ( 96 ). Ultrasound metrics evaluating anterior neck soft tissue thickness and mobility of the neck were found to be important predictors of a difficult laryngoscopy ( 96 ). To date, only one pediatric study evaluating ultrasound for difficult laryngoscopy has been performed that demonstrated good sensitivity (100%) and negative predictive value (100%) but with modest specificity (62%) and positive predictive value (19%) ( 97 ).…”
Section: Current State Of Critical Care Point-of-care Ultrasoundmentioning
confidence: 99%
“…To date, the majority of POCUS airway studies have focused on confirming that the endotracheal tube (ETT) is in the trachea and to identify the cricothyroid membrane for a surgical airway. A recent meta-analysis confirmed there may be some utility in preoperative POCUS airway assessment to predict difficult airway for routine anesthetic care[ 41 ] and there is evidence that these airway scans, when used in combination with the classic clinical airway exams, can reasonably predict difficult airway management [ 42 ]. The prediction of difficult airway relies on measurement of airway anatomical structures, which presents a challenge in rapidly deteriorating trauma patients.…”
Section: Airway Pocusmentioning
confidence: 99%